2015
DOI: 10.1016/j.trpro.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

A Hyperpath-based Network Generalized Extreme-value Model for Route Choice under Uncertainties

Abstract: Previous route choice studies treated uncertainties as randomness; however, it is argued that other uncertainties exist beyond random effects. As a general modeling framework for route choice under uncertainties, this paper presents a model of route choice that incorporates hyperpath and network generalized extreme-value-based link choice models. Accounting for the travel time uncertainty, numerical studies of specified models within the proposed framework are conducted. The modeling framework may be helpful i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The hyperpath routing approach addresses uncertainty and variability of traffic dynamics, where individual traffic agents receive for each origin and destination a tree of alternatives, as opposed to a single route [ 10 , 11 , 13 , 32 ]. It feeds off historical data to discern traffic behavior patterns [ 12 , 33 , 34 ], thus requiring heavy back-end computing to synthesize the pre-trips. TWM is complementary to hyperpaths as it provides different network views for hyperpath calculation.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The hyperpath routing approach addresses uncertainty and variability of traffic dynamics, where individual traffic agents receive for each origin and destination a tree of alternatives, as opposed to a single route [ 10 , 11 , 13 , 32 ]. It feeds off historical data to discern traffic behavior patterns [ 12 , 33 , 34 ], thus requiring heavy back-end computing to synthesize the pre-trips. TWM is complementary to hyperpaths as it provides different network views for hyperpath calculation.…”
Section: Related Workmentioning
confidence: 99%
“…There are many future research possibilities that have been pointed out in the paper: (a) creating optimal static TWM distributions for historical data with evolutionary algorithms, (b) creating dynamic traffic assignment models using TWM based on previous driver experiences as we have shown that they may be critical for TWM adherence, (c) using TWM for zone routing policies as pointed by [ 49 ], (d) applying TWM to hyperpath calculation using techniques described by [ 12 , 34 ], (e) creating evolutionary algorithms and optimization functions for finding local area minimum for routing maps that can cover eventual time-dependent situations, and (f) extension of the MuTraff MTS simulator with mesoscopic simulation engines.…”
Section: Conclusion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In these situations, some drivers would make risky decisions, while others would make risk-averse decisions. The behavioral differences among drivers with uncertainties and risks could produce different route choice ( 24 27 ).…”
Section: Congestion Pricingmentioning
confidence: 99%
“…They found that with a threshold of 80% to define the same route, a combination of link elimination and simulation method can identify 92% of the route people actually use. Ma and Fukuda [ 35 ] compare shortest path routes of taxis with hyperpaths and find that hyperpaths have more explanatory power. GPS data from Taxis may not be consistent with general traffic.…”
Section: Introductionmentioning
confidence: 99%